Wild medicine - exploring medication management challenges in transition and interaction across actors and health sectors related to older adults receiving polypharmacy: a qualitative study - Gitte Wind; Karen-Marie Olesen; Janne Friis Andersen; Line Hillersdal (BMC Geriatrics)
Abstract Background Adverse drug events represent the largest category of incidents health professionals report to regional authorities in Denmark and remain a significant challenge globally. In connection with these events, it is crucial to focus on a specific vulnerable group: people aged 60 and older with polypharmacy (≥ 5 medicines). Existing research has overlooked the importance for the management process of the intricate interaction between various stakeholders, including patients in their homes, primary care physicians, home care nurses, hospital-based physicians, nurses, pharmacists and pharmacy technicians and community pharmacists. The aim of this article is therefore to explore medication management challenges that emerge in transition and interaction across different health care sectors and between different actors. Methods This article used an exploratory qualitative design involving focused field visits and open-ended semi-structured interviews with seven patients aged 60 and older; eight home care nurses in two municipalities; three hospital physicians, three hospital nurses, one pharmacist and two pharmacist technicians in one hospital; two primary care physicians from two clinics; and one pharmacist and one pharmacist technician from one pharmacy. Data collection was followed by thematic analysis. Results Three themes were identified: clashing medicine that captures the conflicts that arise when different practices, systems, and standards collide across health sectors, blind medicine which highlights the gaps in information flow and communication between healthcare actors, and missing medicine which refers to situations where essential medications are unavailable when needed, whether at home, in the hospital, or at the pharmacy. Conclusions This study reveals the intricate nature of medication management and underscores the vital importance of considering the entire medication management process, which involves multiple actors, professional disciplines, electronic systems, physical dispensing systems, and health care sectors. By contributing insights into the practical and systemic nature of medication management challenges, this study aligns with international efforts to address polypharmacy, improve patient-centered care, and strengthen the safety of healthcare delivery.